Adequacy of public maternal care services in Brazil - Sonia Duarte de Azevedo Bittencourt; Rosa Maria Soares Madeira Domingues; Lenice Gnocchi da Costa Reis; Márcia Melo Ramos; Maria do Carmo Leal (BMC, 2016)
Abstract Background In Brazil, hospital childbirth care is available to all, but differences in access and quality of care result in inequalities of maternal health. The objective of this study is to assess the infrastructure and staffing of publicly financed labor and birth care in Brazil and its adequacy according to clinical and obstetric conditions potentially associated with obstetric emergencies. Methods Nationwide cross-sectional hospital-based study "Birth in Brazil: national survey into labor and birth" conducted in 2011-2012. Data from 209 hospitals classified as public (public funding and management) or mixed (public or private funding and private management) that generate estimates for 1148 Brazilian hospitals. Interview with hospital managers provided data for the structure adequacy assessment covering four domains: human resources, medications, equipment for women emergency care and support services. We conducted analysis of the structure adequacy rate according to type of hospital (public or mixed), availability of ICU and the woman obstetric risk using the X 2 test to detect differences in categorical variables with the level of statistical significance set at p <0.05. Results Global rate of adequacy of 34.8 %: 42.2 % in public hospitals and 29.0 % in mixed hospitals (p < 0.001). Public and mixed hospitals with ICU had higher scores of adequacy than hospitals without ICU (73.3 % × 24.4 % public hospitals; 40.3 % × 10.6 % mixed hospitals). At a national level, 32.8 % of women with obstetric risk were cared for in hospitals without ICU and 29.5 % of women without risk were cared for in hospitals with ICU. Inequalities were observed with the North, Northeast and non-capital regions having the lower rates of hospitals with ICU. Conclusions The majority of maternity wards across the country have a low rate of adequacy that can affect the quality of labor and birth care. This holds true for women at high obstetric risk, who suffer the possibility of having their care compromised by failures of hospital infrastructure, and for women at low obstetric risk, who may not receive the appropriate care to support the natural evolution of their labor when in a technological hospital environment.